TiNb2O7/graphene composites as high-rate anode materials for lithium/sodium ion batteries. Issue 11 (26th February 2016) - Li, Shuang; Cao, Xi; Schmidt, Charles N.; Xu, Qian; Uchaker, Evan; Pei, Yi; Cao, Guozhong
Abstract : Layered TiNb2 O7 /graphene composites (TNO/G) are synthesized through a simple freeze drying process. Such a sandwiched structure combined advantages of graphene sheets and TiNb2 O7 (TNO) exhibiting much enhanced rate performance, storage capacity and cycling stability for both lithium and sodium ion insertion. Abstract : Layered TiNb2 O7 /graphene composites (TNO/G) were synthesized through simple direct dispersion and blending in an aqueous solvent followed by a freeze drying process and an annealing treatment under Ar. The graphene sheets are well separated by TiNb2 O7 (TNO) nanoparticles, and simultaneously, the TNO particles are uniformly anchored between the graphene sheets. The combined advantages of graphene sheets and TNO, such as the weight ratio and layered structure, exhibit tremendous benefits for high rate Li ion capability reaching around 180 mA h g −1 at a current density of 38.7 A g −1 (100C rate). Through the synergistic effects of their combination the total specific capacity of TNO/G is higher than the sum of the specific capacity of pure TNO and graphene in their relative ratios. For the study of Na ion capability, as graphene is an active material during the de-sodiation process, a reversible capacity of 340.2 mA h g −1 was obtained from this TNO/G at a current density of 25 mA g −1 . Even at a higher current density of 200 mA g −1, a stable capacity of 200 mA h g −1 can still be obtained. These findings demonstrate the great potential of TNO/G for lithium/sodium ion anodes.